2010
DOI: 10.1074/jbc.m109.083162
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Cucumisin Propeptide as a Potent Inhibitor of Its Mature Enzyme

Abstract: Cucumisin is a subtilisin-like serine protease (subtilase) that is found in the juice of melon fruits (Cucumis melo L.). It is synthesized as a preproprotein consisting of a signal peptide, NH 2 -terminal propeptide, and 67-kDa protease domain. We investigated the role of this propeptide (88 residues) in the cucumisin precursor. Complementary DNAs encoding the propeptides of cucumisin, two other plant subtilases (Arabidopsis ARA12 and rice RSP1), and bacterial subtilisin E were expressed in Escherichia coli in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
(62 reference statements)
2
24
0
Order By: Relevance
“…As previously reported for the PP of cucumisin (30), SBT3PP was found to be insoluble in E. coli and accumulated in inclusion bodies. The recombinant protein was solubilized in 8 M urea and purified to apparent homogeneity by affinity chromatography on nickel-agarose beads under denaturing conditions ( Fig.…”
Section: A V L S K D E L a A L K K L P G F I S A Y K D R T V E P H T supporting
confidence: 58%
See 1 more Smart Citation
“…As previously reported for the PP of cucumisin (30), SBT3PP was found to be insoluble in E. coli and accumulated in inclusion bodies. The recombinant protein was solubilized in 8 M urea and purified to apparent homogeneity by affinity chromatography on nickel-agarose beads under denaturing conditions ( Fig.…”
Section: A V L S K D E L a A L K K L P G F I S A Y K D R T V E P H T supporting
confidence: 58%
“…The data indicate that weak secondary structure is present in the free SBT3PP. SBT3PP thus resembles the PP of cucumisin with respect to secondary structure content and stability (30). In contrast, PPs of mammalian PCs are only marginally stable on their own (with the exception of the PP in PC1 from Mus musculus), and the PPs of bacterial subtilisins are fully unfolded at 25°C (35,37,38).…”
Section: A V L S K D E L a A L K K L P G F I S A Y K D R T V E P H T mentioning
confidence: 99%
“…Inset shows a sketch of the C-terminal flexible region with hydrophobic residues highlighted. (31,32). In this case the C-terminal junction point lies directly within the active site and inhibits activity.…”
Section: Tgmic5 Is Structurally Similar To Proteasementioning
confidence: 99%
“…16,17) In a study of serine protease subtilisins and their propeptides, the functions of subtilisin propeptides as intramolecular chaperons and inhibitors were identified, [18][19][20] and the structure of the subtilisinpropeptide complex was also determined. 20) Structural analysis indicated that the C-terminal strand of the propeptide binds to the subtilisin substrate-binding cleft.…”
Section: Discussionmentioning
confidence: 99%